2017
DOI: 10.1002/pon.4408
|View full text |Cite
|
Sign up to set email alerts
|

Who are happy survivors? Physical, psychosocial, and spiritual factors associated with happiness of breast cancer survivors during the transition from cancer patient to survivor

Abstract: During the reentry period, breast cancer survivors who are hopeful and have a clear purpose in life are more likely to be happy than those who are not. Setting proper life goals might be beneficial to help breast cancer survivors who experience persistent QoL issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Kang et al identified the association between QOL and happiness among cancer survivors. 25 Hirosaki et al reported a correlation between subjective happiness and QOL in community-dwelling elderly Japanese using a 100 mm visual analog scale. 26 In dentistry, Tuchtenhagen et al reported that the oral health-related QOL in schoolchildren was closely associated with the SHS score.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al identified the association between QOL and happiness among cancer survivors. 25 Hirosaki et al reported a correlation between subjective happiness and QOL in community-dwelling elderly Japanese using a 100 mm visual analog scale. 26 In dentistry, Tuchtenhagen et al reported that the oral health-related QOL in schoolchildren was closely associated with the SHS score.…”
Section: Discussionmentioning
confidence: 99%
“…Humor can provide respite for cancer survivors and their loved ones [ 26 ]. Finally, the journey of cancer may not be without moments of happiness or joy [ 27 ]. We will examine the expressions of these positive and negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer and cancer survivors who are happy tend to have a better quality of life and fewer symptoms than unhappy patients do. In addition, happier cancer patients are more likely to report positive expectations about the future; have more life goals; have greater optimism and hope; experience and positive changes within their relationships; are better at coping with problems; and have higher spirituality levels [18,21,33]. Acceptance of the cancer diagnosis and the "path" through treatment are often seen as psychosocial and spiritual transitions that can lead to a restructuring of values and can reflect how patients assess life and their sense of happiness [20,21].…”
Section: Main Findingsmentioning
confidence: 99%